Gendered Epistemology and the Question of Legal Authority: Aisha’s Critique of the Companions - Muhammad Fauzinudin Faiz; Akhmad Zaeni; Muhid Muhid; Ishaq Ishaq; Abdelmalek Aouich (Justicia Islamica, 2026)
This article engages the epistemological dilemma of relying on homogeneity in reliability (ʿadālah and ḍabṭ) among the companions of the Prophet during hadith transmission. In a socio-legal and hermeneutic framework, it analyses Aisha’s interpretive interventions into narrations of significant male companions—Ibn ʿUmar and Ibn ʿAbbās in particular—as manifestations of feminine legal authority in earliest Islamic times. It considers how Aisha’s interactions change how legal reasoning and epistemic authority were constructed during the nascent period of Islamic thought. Drawing upon a hermeneutic textual analysis that is informed by socio-legal and gender-conscious epistemological approaches respectively, the work is concerned with two prominent hadiths in Ṣaḥīḥ al-Bukhārī and Ṣaḥīḥ Muslim: the use of perfume prior to iḥrām and the nadhr involving the Prophet’s camel al-ʿAdhbāʾ. Analysis demonstrates that Aisha’s interventions do not deny hadith itself or the companions but instead emphasise interpretive coherence, empirical proof and legal reasoning grounded in first-hand prophetic experience. Her epistemological agency, on the other hand, stands as an early female presence in the manufacture of hadith-based legal reasoning that stands at divergence from the gendered paradigm and extends an epistemology based on dialogue. By re-assessing Aisha’s methodological interventions, the study plays into a more comprehensive debate about gendered knowledge production as well as the epistemological credibility of Islamic legal thought and provides readers with a framework for rethinking authority, gender and interpretation in Islamic scholarship in the present moment.